Carrying Capacity of Education Facilities in Banawa Sub-District, Central Sulawesi Province - Ibnu, Moh; Saputra, Iwan Alim; Maliki, Rendra Zainal; Budianta, Aziz; Ali, Zaenudin (Tunas Geografi, 2023)
Education is a basic human need with the aim of achieving high productivity. The results of field surveys in Banawa Regency show that the availability of educational facilities to meet educational needs, based on population projections in 2044, has not yet reached the optimal level. Therefore, careful planning is needed in improving and placing educational facilities. This research aims to evaluate the availability of educational facilities according to the needs of the population, by applying an analysis of the carrying capacity of facilities based on public service standards regulated in SNI 03-1733-2004 concerning urban area planning. The methodology used involves analysis of the carrying capacity of facilities to determine the population's need for educational facilities, population projections using geometric formulas to calculate the expected number of residents in the projected year, as well as spatial analysis using Geographic Information System (GIS) software to assess the distribution of facilities. education in Banawa District. The findings from this research indicate that currently there are 82 units of educational facilities in Banawa District, consisting of 39 PAUD units, 31 elementary school units, 8 junior high school units, and 4 high school units. However, additional educational facilities are needed by 7 PAUD units, 5 elementary school units, 4 junior high school units and 8 high school units in Banawa District.Keywords: Education, Facilities, Carrying Capacity, Banawa